2012
DOI: 10.1016/j.bbr.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cyclin D2 impairing adult brain neurogenesis alters hippocampal-dependent behavioral tasks without reducing learning ability

Abstract: The exact function of the adult brain neurogenesis remains elusive, although it has been suggested to play a role in learning and memory processes. In our studies, we employed cyclin D2 gene knockout (cD2 KO) mice showing impaired neurogenesis as well as decreased hippocampal size. However, irrespectively of the genetic background of cD2 KO mice, this phenotype resulted in neither deficits in the hippocampal-dependent learning ability nor the memory formation. In the present study, cD2 KO mice and control litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 48 publications
2
51
1
Order By: Relevance
“…On the contrary, the immobility was reduced in these mice. We have observed before cD2 KO animals to be more active and explorative (Jedynak et al, 2012;Ben Abdallah et al, 2013). Please note, we were still able to increase immobility in mutant mice by UCMS and again reduce it through chronic fluoxetine treatment.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…On the contrary, the immobility was reduced in these mice. We have observed before cD2 KO animals to be more active and explorative (Jedynak et al, 2012;Ben Abdallah et al, 2013). Please note, we were still able to increase immobility in mutant mice by UCMS and again reduce it through chronic fluoxetine treatment.…”
Section: Discussionmentioning
confidence: 53%
“…There is also possibility of compensatory mechanisms to operate in these mice (discussed in Jaholkowski et al, 2009), however, the model is recognized as valuable and adequate tool in the field (for review see Frankland, 2013). The results obtained with the use of cD2 KO mice suggested the lack of relevance of adult brain neurogenesis for learning and memory in general (Jaholkowski et al, 2009) e a view which is now widely accepted (e.g., Sahay et al, 2011) e while suggested and/or confirmed the role of this process in particular aspects of learning (Ben Abdallah et al, 2013), smell detection (Jaholkowski et al, 2009), species-typical behaviors (Jedynak et al, 2012), and alcohol consumption (Jaholkowski et al, 2011). Most of transgenic models with manipulated adult hippocampal neurogenesis, in contrast to our model, do not achieve complete ablation of newborn neurons.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…27 In cyclin D2-knockout mice, the brain size is smaller and adult neurogenesis is dramatically impaired. [28][29][30][31] Cyclin D2 is essential for expansion of the NSPCs in both embryonic and adult brains, but what is the significance of the biased localization of cyclin D2 in the basal endfoot of the APs? Figure 1.…”
Section: Cyclin D2 and Brain Evolutionmentioning
confidence: 99%